Key/core competencies : synthesis of related work undertaken within the Eurotecnet programme (1990-94) - (:unkn) unknown (Office for Official Publications of the European Communities, 1995)
"This document is an attempt to assemble in a synthetic form the main work to date followed in the EUROTECNET Programme on key/core competencies. The first three chapters of this document outline the context in which the concept of key/core competencies was developed, how they can be described and implemented, and the training implications resulting from technological change and new forms of work organisation. Chapter four describes the involvement of some of the projects in the development of key/core competencies and the activities related to this concept which have taken place since the beginning of the EUROTECNET Programme. Chapter five highlights the concept of key/core competencies in an European context. Chapter six outlines the broad context for future developments and presents some recommendations for the transition to the LEONARDO Programme." (Excerpt, BIBB-Doku)
Keywords: I 2.2 Europa; G 2.2.1 Technologisierung; G 2.3 Wandel von Arbeit & Wirtschaft; Europäische Union; Technische Entwicklung; Tätigkeitswandel; Kompetenzentwicklung; Schlüsselqualifikation